Factors Affecting Consumers on the Purchase of Islamic Book - Sidqi, Teuku; Yazid, Muhammad Hafis; Ridwan, Muhammad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
Publishing is one of the supporting components in the process of the emergence of the history of the world of print media in the world and in Indonesia in particular. In general, publishing is a business entity that bridges the ideas of an author of fiction and non-fiction books so that the publisher can publish it to the general public, both those who already know him and those who do not know him. This study aims to see the effect of products, prices, promotions and processes on the purchase of Islamic books at PT. Grafindo King. The research was conducted with a quantitative approach and used multiple regression analysis with a questionnaire instrument given to 100 respondents. The results showed that partially and simultaneously product prices, promotions and processes significantly influence the purchase of books at PT. Grafindo King. With a level of determination the value of the multiple correlation coefficient of 0.903 is positive, meaning that the influence of product, price, promotion, and process variables on purchases is very strong, or 90.3% of the dependent variable can be influenced by the independent variable, while 0.7% is influenced by other variables not